2006
DOI: 10.1063/1.2374191
|View full text |Cite
|
Sign up to set email alerts
|

Gate leakage mechanisms in strained Si devices

Abstract: This work investigates gate leakage mechanisms in advanced strained Si/ SiGe metal-oxide-semiconductor field-effect transistor ͑MOSFET͒ devices. The impact of virtual substrate Ge content, epitaxial material quality, epitaxial layer structure, and device processing on gate oxide leakage characteristics are analyzed in detail. In state of the art MOSFETs, gate oxides are only a few nanometers thick. In order to minimize power consumption, leakage currents through the gate must be controlled. However, modificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…3͑b͒. 25 Therefore, both compressive and tensile stresses along ͓110͔ cause a decrease in the trap activation energy at P b0 and P b1 centers, ⌬ T ͑͒ Ͻ 0, 9,11,26 resulting in an increase in trap-assisted gate leakage current for both gate and substrate injections, as shown in Fig. 1͑b͒.…”
Section: Impact Of Mechanical Stress On Direct and Trap-assisted Gatementioning
confidence: 93%
See 1 more Smart Citation
“…3͑b͒. 25 Therefore, both compressive and tensile stresses along ͓110͔ cause a decrease in the trap activation energy at P b0 and P b1 centers, ⌬ T ͑͒ Ͻ 0, 9,11,26 resulting in an increase in trap-assisted gate leakage current for both gate and substrate injections, as shown in Fig. 1͑b͒.…”
Section: Impact Of Mechanical Stress On Direct and Trap-assisted Gatementioning
confidence: 93%
“…6 It has been reported that mechanical stress affects trap generation in metal-oxide-semiconductor ͑MOS͒ devices, 9,10 but less attention has been paid to mechanical stress-altered trap-assisted gate tunneling current. 11 In this work, we report for the first time the effects of uniaxial stress on trap-assisted gate tunneling current by using controlled applied mechanical stress and constant voltage stress ͑CVS͒.…”
Section: Impact Of Mechanical Stress On Direct and Trap-assisted Gatementioning
confidence: 99%
“…12 A possible explanation is that the traps responsible for enhanced PF conduction in the device operative regimes are due to Ge out diffusion into the gate oxide. 3,7,8,13 On wafer gate current, low frequency noise measurements have been done by using a dedicated noise measurement system. 9 The gate current power spectral density ͑PSD͒ for both Ge pMOSFETs and reference Si pMOSFETs show a 1/ f ␥ behavior with ␥ nearly equal to 1.…”
mentioning
confidence: 99%
“…Most studies of oxides in strained Si devices were entirely focused on the oxide/semiconductor interface quality ͑e.g., fast interface states͒ and the detrimental impact of Ge diffusion from the SiGe virtual substrate to the Si surface. 18 The impact of virtual substrate Ge composition, strained Si channel thickness, virtual substrate material quality, and thermal budget was examined. The paucity of comprehensive experimental data is unfortunate since the increased electron affinity of tensile strained Si compared to that of bulk Si theoretically leads to a reduction in tunneling currents.…”
Section: Introductionmentioning
confidence: 99%